(untitled) (CAHIERS MAGELLANES-NS, 2024)
The identification of the rightful heirs to the sacred text is a topic discussed in verse 32 of Surah Fatir. Scholars have proposed three main viewpoints: some argue that the prophets are the inheritors, others suggest that the believers hold this position, and yet another perspective posits that the Prophet's community and Islamic scholars are potential candidates. Additionally, certain Islamic traditions present the Imams as divinely chosen successors and inheritors of the Book, specifically referring to the Quran. This study explores and substantiates the latter viewpoint through a comprehensive examination of Quranic verses, traditional accounts, and literary sources.